Nationality and Statelessness: A Handbook for Parliamentarians (2005)
This handbook aims to provide parliamentarians with a broad description of the international principles regulating nationality and statelessness. International law gives States broad discretion with which to define their initial body of citizens and the conditions for acquiring, losing, and retaining citizenship. However, human rights principles developed throughout the 20th century limit this latitude if it results in statelessness and/or if it is applied in a discriminatory manner.